Cute Chaucer. (3rd April 2018) - Kao, Wan-Chuan
ABSTRACT: Reading Sir Thopas through cuteness shifts critical attention from the tale's generic classification to questions of aesthetics and affect. The production of cute features through infantilization and feminization triggers tender caretaking and sadistic aggression; the cute object is paradoxically held gently and squeezed violently. Under the duress of the cute response, the Chaucerian narrator, Thopas, and the text become deformed. The flattening of physical and textual bodies leads to the obliteration of verticality and depth. Drawing on the superflat movement in Japanese contemporary art, I argue that cuteness in Sir Thopas effects a compression of the text's narrative layers and semiotic networks. Mirroring the horizontal, non-linear organization of the poem's layout in medieval manuscripts, desire moves sideways across Sir Thopas . The lateral mobility and the agglutinating property of cuteness allow it to adhere to and cutify objects in its vicinity; the catalogues of romance tropes in Sir Thopas thereby function as cute object clusters within a late medieval middling household. Too much sticky sweetness, however, results in revulsion and not adoration. When the Host interrupts Chaucer and compares the poem to excrement, he enacts the labile fungibility of cuteness and disgust. Sir Thopas is both feces and a dainty thing.